2012
DOI: 10.1002/eji.201142346
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsion mucosal adjuvant uniquely activates cytokine production by nasal ciliated epithelium and induces dendritic cell trafficking

Abstract: While the nasal mucosa is a potentially useful site for human immunization, toxin-based nasal adjuvants are generally unsafe and less effective in humans. Safe mucosal adjuvants that activate protective immunity via mucosal administration are highly dependent on barrier antigen sampling by epithelial and dendritic cells. Here, we demonstrate that protein antigens formulated in unique oil-in-water nanoemulsions results in unique trans-cellular antigen uptake in ciliated nasal epithelial cells, leading to delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 52 publications
(64 reference statements)
4
52
0
Order By: Relevance
“…produced protective immunity to a variety of pathogens, including anthrax, vaccinia, HIV, influenza, and hepatitis B surface Ag (32)(33)(34)(35). Recently, we also demonstrated that W 80 5EC NE increases Ag uptake and trafficking by epithelial cells and DCs, resulting in both apoptosis and DC maturation (36,37). These findings suggest that W 80 5EC NE produces unique activation of epithelial cells and DCs on the nasal mucosa.…”
mentioning
confidence: 68%
“…produced protective immunity to a variety of pathogens, including anthrax, vaccinia, HIV, influenza, and hepatitis B surface Ag (32)(33)(34)(35). Recently, we also demonstrated that W 80 5EC NE increases Ag uptake and trafficking by epithelial cells and DCs, resulting in both apoptosis and DC maturation (36,37). These findings suggest that W 80 5EC NE produces unique activation of epithelial cells and DCs on the nasal mucosa.…”
mentioning
confidence: 68%
“…Interestingly, NE did not enhance uptake in DCs or macrophages in vitro (not shown), emphasizing the importance of mucoadhesion-facilitated epithelial cell antigen uptake, and supporting our observations on the pivotal role of ciliated epithelial cells in the NE-mediated immune response. 18 …”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that NEs serve as much more than inert vehicles for antigen delivery, and that these formulations are able to activate cytokine production by epithelial cells in the nasal passage, and induce DC trafficking. 18 The simple in vitro screening methods presented here along with our in vivo immunogencity studies provide the first steps to understanding the relationship between the physicochemical properties of emulsion surfactants and adjuvant effectiveness. We demonstrate that NEs with very diverse sets of surface and adhesion properties can be produced by variation of the surfactant combinations.…”
Section: Discussionmentioning
confidence: 99%
“…9 A recent study indicated that nanoemulsion adjuvants potently and powerfully induce broad mucosal immune responses. 10 However, no nanoemulsion adjuvant has been reported to significantly enhance both the intramuscular systemic and nasal mucosal immune responses.…”
Section: Introductionmentioning
confidence: 99%